Viscoelastic boundary layer MHD flow through a porous medium over a porous quadratic stretching sheet - Kumar Khan, S.; Sanjayanand, E. (Archives of Mechanics, 2004)
Boundary layer MHD flow of a viscoelastic fluid in a porous medium over a porous stretching sheet has been presented in this article. A typical choice of quadratic stretching of the boundary, having a quadratic part in velocity parallel to the boundary sheet and a linear mass flux in the velocity normal to the stretching sheet, constitutes the boundary conditions of the problem. The effect of various values of nondimensional physical parameters on streamline patterns and skin friction coefficient are discussed. Some of the important findings of the article are: (a) the flow is enhanced by the positive values of linear mass flux parameter and suppressed by the negative values of linear mass flux parameter; (b) the effect of permeability parameter is not significant when linear mass flux parameter takes zero or negative values; (c) the combined effect of reduction of the values of permeability parameter, Hartmann number and linear mass flux parameter is expected to reduce largely the values of skin friction coefficient.